A CuI/CuIII prototypical organometallic mechanism for the deactivation of an active pincer-like CuI catalyst in Ullmann-type couplings. Issue 62 (21st July 2017) - Rovira, Mireia; Jašíková, Lucie; Andris, Erik; Acuña-Parés, Ferran; Soler, Marta; Güell, Imma; Wang, Ming-Zheng; Gómez, Laura; Luis, Josep M.; Roithová, Jana; Ribas, Xavi
Abstract : Decomposition pathways in Ullmann C–O couplings have been studied by helium tagging IRPD and DFT studies, supporting aryl–Cu III intermediate species. Abstract : Unraveling the mechanistic details of copper-catalyzed arylation of nucleophiles (Ullmann-type couplings) is a very challenging task. It is a matter of intense debate whether it is a radical-based process or an organometallic redox-based process. The ancillary ligand choice in Ullmann-type couplings plays a key role in such transformations and can strongly influence the catalytic efficiency as well as the mechanism. Here, we show how a predesigned tridentate pincer-like catalyst undergoes a deactivation pathway through a Cu I /Cu III prototypical mechanism as demonstrated by helium-tagging infrared photodissociation (IRPD) spectroscopy and DFT studies, lending a strong support to the existence of an aryl–Cu III species in the Ullmann couplings using this tridentate ligand.